Assessing prospect and challenges of e-learning in teacher education program aftermath of covid-19 pandemic: teacher educators’ views - Julius Michael Egbai; Eke Ogbu Eke; Ijeoma F Ubochi (Center for Humanities and Innovation Studies, 2021)
The study aims at assessing teacher educators’ views on the prospect and challenges of e-learning in teacher education program aftermath of the Covid-19 pandemic. The population consists of 1321 academic staff of Alvan Ikoku College of Education Owerri (AIFCE). Two Schools out of the seven schools in Alvan Ikoku Federal College of Education were purposively selected for the sample size of 249 academic staff. Researchers made an assessments questionnaire titled” Teachers Views on Prospect and Challenges eLearning in Teacher Education Program Questionnaire (TVPCETEC) was used for data collection. It has a reliability coefficient of 0.77 determined through the Pearson Product Moment Correlation Coefficient. The data collected were analyzed using mean and standard deviation in answering the research questions. The study showed that teacher educators are of the view that e-learning is the key for effective teacher education program vis-vis the Covid-19 pandemic, which has called for social distance protective protocols. Challenges to effective e-learning, such as in teacher education, were also identified. But despite the challenges facing e-learning in teacher education programs, teacher educators accepted that e-learning is the key to limitless possibilities in education and should be fully embraced. It is recommended that Colleges of Education liaise with relevant authorities in benchmarking teacher education programs with e-learning. It will help tackle the digital divide among lectures and students for effective implementation of learning in teacher education programs.